شركة المستقبل للحوالة والصرف الصومالية: دراسة فقهية تقويمية - دخني، محمد غالب (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
By conducting a meticulous exploration and legal grounding, this research strives to explicate the rulings on Al-Mustaqbal Company for remittance and money exchange followed by analysing the causes and factors of emergence and headways of these companies therein. Subsequently, it expounds the concept of remittance (Hawalah) and currency exchange (Sarf) and their types, models and conditions in light of Islamic jurisprudence. In addition, the researcher discourses the rulings on the combination of mudurabah and musharakah, shedding light on the rulings on fund investments in different areas and modern applications of remittance and money exchange carried out by these companies. Finally, the research concludes with a chapter consisting of a survey as a practical model conducive to analyzing the results of the questionnaires distributed to the relevant parties and drawing conclusions from them. The researcher adopted the inductive method to collect relevant scientific data and critical method to conduct a thorough investigation of various juristic opinions. In addition, the researcher used comparative method to deliberate on the various juristic opinions and their evidences followed by a discussion in preferring one opinion to others. In order to verify the commitment of Al-Mustaqbal Company to the rules and regulations of Shariah, the researcher conducted interviews with the founders and officials thereof. This study recommends formulathng vigorous engagement with international financial bodies and institutions for undertaking in-depth studies and benefitting from the Somali experiences, thus to transfer them to Arab people who currently go through the same plight which was suffered by Somali people due to the civil war and diaspora decades ago.